Kelas Persiapan Persalinan secara Holistik terhadap Kecemasan dan Self Efficacy Menghadapi Persalinan pada Ibu Hamil Trimester III - Dheanda, Tavazuli Clara; Santoso, Bedjo; Wahyuni, Sri (Journal of Telenursing (JOTING), 2024)
This study aims to produce a holistic childbirth preparation class model to reduce anxiety and increase self-efficacy in facing childbirth in pregnant women in the third trimester. The method used is Research and Development (R&D). The results of the study showed that the application of the holistic childbirth preparation class model effectively reduced anxiety with a p-value of 0.000 (<0.05) and increased self-efficacy in facing childbirth with a p-value of 0.000 (<0.05). In conclusion, the childbirth preparation class is feasible and its application is effective in reducing anxiety and increasing self-efficacy in facing childbirth in pregnant women in the third trimester. Keywords: Holistic Midwifery Care, Anxiety, Childbirth Preparation Class, Self Efficacy